Perceived discrimination, health and mental health among immigrants in Norway: the role of moderating factors - Melanie Lindsay Straiton; Arild Kjell Aambø; Rune Johansen (BMC, 2019)
Abstract Background Ethnic discrimination is a relatively common experience among immigrants and ethnic minorities. The experience of discrimination can have detrimental effects on an individual's health and well-being. This study investigated the association between perceived discrimination and general health and mental health among immigrants in Norway, in order to identify potential protective factors. Methods Using data from the Living Conditions Survey among Immigrants 2016, our sample consisted of 4294 participants aged 16-66 years from 12 different countries. Participants were asked about a variety of themes including health and mental health, perceived discrimination, sense of belonging and language proficiency. Results Around 27% of participants reported perceived discrimination. While perceived discrimination was not associated with general health, logistic regression analyses indicated that it was associated with 1.86 higher odds of mental health problems, even after adjusting for sociodemographic and psychosocial variables. Further, interaction analyses suggested that sense of belonging and trust in others moderated the relationship. Those with higher levels of trust did not have increased odds of mental health problems when experiencing discrimination, while those with low levels of trust did. In line with rejection sensitivity theory, the association between perceived discrimination and mental health was stronger for participants who had a strong sense of belonging to their own country of origin but not to Norway compared with those who had a sense of belonging to both. Conclusions Improved integration strategies could potentially improve the mental health of immigrants as well as increase the acceptability of diversity, which in turn, could reduce discrimination towards immigrants. Limitations and suggestions for further research are discussed.